STATUS HUKUM ANAK YANG LAHIR DARI PERKAWINAN CAMPURAN ANTAR KEWARGANEGARAAN MENURUT UNDANG-UNDANG NO 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Fitry Fatrysya; Annisa Nurlaelani Sudiro; Faulin Hasna Dalilah (Cross-border, 2022)
In carrying out marriages, many people marry partners of different nationalities. From this, of course, creates problems in determining the citizenship status of the child. In Indonesia, there is a legal status for children born from mixed marriages between nationalities, but legally the child will have problems related to the acquisition of the rights that the child will get. The purpose of this study is to describe the legal status of children so that there is no apatride (not having citizenship status) or bipatride (having dual citizenship status). The method used in this research is the literature review method or literature study, as well as the analysis of the study using qualitative analysis. The author uses primary legal materials that are binding and also secondary legal materials as references. The results of this study that the legal protection of the position of children born in mixed marriages in Indonesia has received protection in Law no. 32 of 2002 concerning the protection of children contained in article 5 which reads "every child has the right to a name as self-identity and citizenship status", therefore every child has the right to get preventive legal protection to ensure legal certainty as an Indonesian citizen. the obligation to protect children as citizens and also the obligation to guarantee the education of other children's rights initially, to determine citizenship.